2004
DOI: 10.1364/ol.29.001200
|View full text |Cite
|
Sign up to set email alerts
|

Full-field heterodyne interference microscope with spatially incoherent illumination

Abstract: A heterodyne interference microscope arrangement for full-field imaging is described. The reference and object beams are formed with highly correlated, time-varying laser speckle patterns. The speckle illumination confers a confocal transfer function to the system, and by temporal averaging, the coherence noise that often degrades coherent full-field microscope images is suppressed. The microscope described is similar to a Linnik-type microscope and allows the use of high-numerical-aperture objective lenses, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…For point-scanning SH-SLCHM (P-SH-SLCHM), the corresponding frequency shift to achieve 10frames/s with en-face images of 500×500 pixels is ~1900Hz. In fact, use of two AOMs to generate a relative frequency shift between reference and object fields has been well researched in DH [30][31][32], where a frequency shift of several Hz is generated by two AOMs to obtain accurate phase-shifted holograms to achieve the complex field. Their work has demonstrated that it is possible to realize accurate frequency shift as low as several Hertz to milliHertz.…”
Section: Introductionmentioning
confidence: 99%
“…For point-scanning SH-SLCHM (P-SH-SLCHM), the corresponding frequency shift to achieve 10frames/s with en-face images of 500×500 pixels is ~1900Hz. In fact, use of two AOMs to generate a relative frequency shift between reference and object fields has been well researched in DH [30][31][32], where a frequency shift of several Hz is generated by two AOMs to obtain accurate phase-shifted holograms to achieve the complex field. Their work has demonstrated that it is possible to realize accurate frequency shift as low as several Hertz to milliHertz.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to completely parallelize confocal image acquisition is to combine interferometric detection with spatial coherence gating [13][14][15][16][17] However, the main advantage of parallelization-faster image acquisition-has thus far been mitigated by the lack of an appropriate light source. Traditional low-spatial coherence sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…line-scan confocal microscopy [8][9][10]) to improve imaging speed, but cross-talk limits this approach to weakly scattering samples [11]. Spectral encoding can provide parallelization in one dimension without cross-talk by using a grating to map different wavelengths to a line on the sample; however, scanning in the second dimension is still required to form an image [12].An alternative approach to completely parallelize confocal image acquisition is to combine interferometric detection with spatial coherence gating [13][14][15][16][17] However, the main advantage of parallelization-faster image acquisition-has thus far been mitigated by the lack of an appropriate light source. Traditional low-spatial coherence sources (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This arrangement is usually only used in single point interferometers due to the practical challenges associated with capturing widefield time varying fringe patterns. However some systems have been developed to capture real time heterodyne interference patterns in the widefield region at modest modulation frequencies [5][6][7][8][9]. In a previous paper [9], we demonstrated that this could be accomplished for the widefield in the megahertz frequency range using a prototype modulated light camera (MLC).…”
Section: Introductionmentioning
confidence: 99%